Al-Jazari contribution on the development of water supply systems - Kamaruddin, Shafie; Shuriye, Abdi Omar (IIUM Press, 2011)
The objective of this study is to highlight AI-Jazari contribution in the development of water supply system. The significance of the study is that it places emphais on AI-Jazari and his inventions which laid the foundation for the machinery of irrigation and machine design. The methodology adopted in this research is library based and data is collected from reliable resources. The main focus of the chapter is to understand AI-Jazari's contribution in water raising machines which some of it can still be seen in several contemporary machines. The chapter explores the fifth chapter of his book which presents five different, useful inventions mainly to raise water for irrigation and domestic purpose